NOVEL CAHAYA CINTA PESANTREN KARYA IRA MADAN (Kajian Psikologi Sastra dan Nilai Pendidikan Budaya Islam) - Siti Aminah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study describes the Psychology of Literature and Value of Islamic Cultural Education. This research is a qualitative research using descriptive method and content technique. The results of this study indicate that the interrelationships between elements in the novel Cahaya Cinta Pesantren can build a braided story full of conflict and have a reinforcement on the theme. In addition, the message or message author submitted through the educational value consists of: (a) the value of the soul of simplicity, which contains the element of the power of the heart to face the struggle of life with all difficulties, (b) the value of the soul of self-reliance, the soul of self-help, the value of the soul Ukhuwah Islamiyah, ie the atmosphere of the intimate brotherhood so that all the pleasures are felt together with the fabric of religious feeling, (d) the value of the soul of freedom, that is free in determining the future in choosing the way of life in the society, (e) the value of the soul of keiklasan, because driven by the desire to obtain certain advantages. In addition, the psychology of women in the novel Cahaya Cinta Pesantren by Ira Madan has five needs, namely: the need for love, physiological needs, the need for sense of security, the need for actualization, the need for a sense of price.Keywords— light love pesantren, literary psychology, and educational values.